A model explaining the anomalous fading effect in thermoluminescence (TL). (January 2023) - Lawless, J.L.; Chen, R.; Pagonis, V.
Abstract: An energy-level model consisting of an electron trap, a hole trap and a hole recombination center is proposed to explain the anomalous-fading effect of thermoluminescence which has been observed in several materials. The present model is related to a thermoluminescence glow-curve consisting of two peaks. The relevant set of coupled differential equations is considered and a set of the relevant parameters is chosen. The equations are solved both by making plausible analytical approximations and numerically by using a Matlab solver; the results of the two approaches are in very good agreement. The simulated sample is excited at 100K and then held at room temperature or lower for different lengths of time before simulating the heating stage. It is found that as expected, the low-temperature peak at ∼400K decays very quickly and quite anomalously, the high-temperature peak at ∼570K is also fading much faster than expected for a peak occurring at this temperature. The dependence on the fading temperature, an effect which has been found in some materials is also demonstrated in the simulations. The numerical simulations and the analytical approximations can explain these results and show why this decoupling between the peak temperature and the fading takes place. Highlights: A new model explaining anomalous fading of thermoluminescence (TL) is presented. The model includes an electron trap, a hole trap and a hole center. Simulation of the processes involved using a matlab ode solver is reported. Theoretical treatment with approximations yields results similar to the simulations.